Just what the doctor ordered: medicinal alcohol, opioid prescriptions, and the accessibility of folk devils - Stout, Joshua H. (Deviant behavior, 2023)
A critical component in the formation of moral panics rests on the successful construction of folk devils. The successful construction of folk devils in a moral panic has often relied on both the media and the general public vilifying those who occupy a lower social status, depicting these vilified individuals as culpable for specific social problems. This paper conducts a historical comparison between the prescription of medicinal alcohol during prohibition and the prescription of opioids during the opioid epidemic to address the question of when, and under what conditions, respected professionals get blamed for a social problem and labeled deviant. Both periods were marked by similar behavior of doctors, where some doctors prescribed these substances for profit. However, doctors during prohibition were not depicted as folk devils, nor did a moral panic ensue regarding their medicinal alcohol prescribing practices. During the opioid epidemic, pain management doctors were depicted as folk devils supporting the moral panic surrounding prescription opioids. This paper expands upon moral panics theory by demonstrating that the accessibility of folk devils influences the successful establishment of a moral panic.